Transitional Justice and the Limits of What is (possibly) Punishable. Reflections on the Legitimacy of the Peace Process in Colombia (2018)
This study proposes that the Colombian peace process has ratified that transitional justice finds limits in human rights related to three aspects: a) amnesty or pardon measures for serious violations of human rights are not possible; b) measures of impunity are only possible if the duty of providing reparation to the victims was fulfilled; and c) penal or retributive measures that imply a different treatment for those who incurred in human rights violations in the context of the armed conflict are only possible if the State provides certain minimum rights in the victims’ reparation. The 2016 Peace Agreement and the jurisprudence of the Colombian Constitutional Court differ from the norms elaborated by the Inter - American Court of Human Rights on the duty to investigate and sanction violations of human rights.